Метро до Африки: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2008)
Экземпляры: ф. 2 (20090330) / Инвентарный номер: 94136 / Цена: 60.00 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6